[PP.03.09] CARDIOVASCULAR RISK PROFILE IN THE FRENCH CARIBBEAN: SERIOUS SOCIAL INEQUALITIES. (September 2016) - Carrère, P.; Harchaoui, Y.; Hélène-Pelage, J.; Atallah, A.; Lang, T.; Inamo, J.
Abstract : Objective: The French West Indies are affected by high levels of early mortality stemming from cardiovascular disease (CVD) and wide social discrepancies. However, the link between CVD risk and socioeconomic factors remains ambiguous in the Caribbean region. Our objective was to assess the relationships between overall CVD risk and socioeconomic level in a French Caribbean population. Design and method: A multicenter cross-sectional study was conducted in Guadeloupe between July and December 2014. The source population consisted of all patients receiving a systematic periodic health examination funded by social security during the study period. The collection of socio-demographic, clinical and biological data was standardized. Education level was used as a proxy for socioeconomic level. Hypertension was defined by antihypertensive treatment or mean of three measurements of blood pressure > = 140/90 mmHg. Diabetes was defined by diabetes treatment or fasting plasma glucose > = 7 mmol/L and glycated hemoglobin > = 6.5%, controlled diabetes by glycated hemoglobin < 7%. Tobacco smoking was ascertained by self-report, abdominal obesity by measured waist circumference > = ESH thresholds. Global CVD risk was estimated with the Framingham Risk Score for Use in Primary Care (Agostino et al, 2008). Analyses focused on subjects aged 30–74 with complete data sets (n = 1764). Multilevel logistic regression was used. Results: Regardless of center, age and education level, the risks of obesity and diabetes for women were twice as high as for men. Independently of center and age, low education level was associated with higher rates of obesity and diabetes in women, and with hypertension in both sexes. The median global CVD risk was estimated at 5.3% (Q1 = 2.5%; Q4 = 10.5%). Among subjects with an education level lower than middle school diploma, 13.7% presented a global CVD risk > = 20%, compared with 5.5% among subjects with higher levels of education (center adjusted OR = 2.7; p < 0.001). Among high-risk subjects, 79% of subjects treated for hypertension and 72% of subjects treated for diabetes had uncontrolled conditions. Conclusions: Reducing social inequalities in health requires a truly comprehensive approach to CVD risk. Prevention strategies should be differentiated by sex. A net improvement in quality of care is needed.